ABO groups as a risk factor for myocardial infarction in the population of Bosnia and Herzegovina - Ermina Mujičić; Nermir Granov; Armin Šljivo; Amina Selimović (Medicinski glasnik, 2020)
Aim: To investigate the association of ABO blood types and appearance of myocardial infarction (MI) among the population in Bosnia and Herzegovina. Methods: This was a cross sectional study conducted at the Department for Cardiovascular Surgery at the Clinical Centre of the University of Sarajevo from January 1 st to December 31 st 2019. Patients were divided into two groups, defined by their blood type, A (N=91) and non-A (N=109). ABO blood groups were determined using standard agglutination techniques. Information regarding history of MI was taken from their medical documentation during the preparation for surgery. Results: In total 200 patients were involved in this study. The study sample consisted of 151 (74.5%) males and 49 (25.5%) females. Mean age was 62.98 ± 7.73. Various risk factors associated with myocardial infarction were tobacco 92 (46.0%) and alcohol 54 (27.0%) consumption, obesity 77 (38.5%), diabetes mellitus 47 (23.5%) and hypertension 91 (45.3%). Being A blood type (OR=3.308; 95% Cl 1.317-8.311; p=0.011) and being male and having hypertension (OR=3.086; 95% Cl 1.262-7.545; p=0.013) significantly increased the risk for the development of MI among young adults. Patients with A blood type were significantly younger [median 58.0 vs. 63.0; U = 2738.5; p =0.027] when they developed MI compared to non-A blood type. Conclusion: The age of myocardial infarction occurrence in the population of Bosnia and Herzegovina is lower in patients with blood group A compared to non-A blood types.
Keywords: acute myocardial infarction; A blood type; ABO blood groups; coronary artery disease; risk factors